2011
DOI: 10.1111/j.1365-2354.2011.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Iranian cancer patients and their perspectives: a qualitative study

Abstract: The incidence of cancer is continuing to rise in Iran. More people are now surviving cancer. They may require different kinds of care and support from those traditionally available. The expression of needs and how they are met in different cultural contexts can inform local assessment of needs and provide insights for initiatives in holistic cancer care. This study explores Iranian cancer patients' needs from patients' perspective. A qualitative design that consists of interviews, field notes and specified dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…This reaction may be considered as criticism because they did not accept their mother as she was. Criticism has likewise been found in past research (Moradian et al, 2012).…”
Section: Changes In the Familymentioning
confidence: 71%
“…This reaction may be considered as criticism because they did not accept their mother as she was. Criticism has likewise been found in past research (Moradian et al, 2012).…”
Section: Changes In the Familymentioning
confidence: 71%
“…There are no any studies investigated the problems faced by Iranian cancer survivors distinctively. Although, some other studies showed that Iranian cancer patients have experienced many complications such as marital problems (Azizi et al, 2010), anxiety and depression (Malekian et al, 2007), social isolation (Rahemi, 2006), physical problems (Abdollahzadehet al, 2014) and financial distress (Moradian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is the third leading cause of death in Iran , with annual incidence rates of 120.1 and 134.7 per 100,000 in women and men, respectively, and annual mortality rates of 41.2 and 60 per 100,000 in women and men, respectively . Although more than 90% of Iranian people have health insurance coverage, cancer care is assumed by patients to be costly for them due to copayments at time of service . However, access to cancer care centers is possible for most cancer patients and they are mostly satisfied by the provided services .…”
Section: Introductionmentioning
confidence: 99%